Electronic Excited States of the Dihalomethanes, \(\rm CH_2X_2 \ (X=Cl, Br, I)\) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
The vacuum ultraviolet (VUV) photoabsorption spectra of the dihalomethanes \(\rm CH_2X_2 \ (X=Cl, Br, I)\) are studied using synchrotron radiation in the energy region 6–11.8 eV (\(\sim\)49,000–95,200 cm\(^{âˆ’1}\)). A detailed comparison is made to identify similarities, differences and trends in the spectra and excited state structure of these three molecules. The electronic spectra of the dihalomethanes in this region are dominated by Rydberg series of \(ns\), \(np\) and \(nd\) type. Quantum defect analysis reveals that the Rydberg series in all the dihalomethanes originate from the four outermost halogen lone pair non-bonding orbitals. On going from Cl to I, the energy difference between the first four ionization potentials decreases which as a consequence leads to spectral congestion and complications in spectral assignments. In all three molecules, several Rydberg transitions are accompanied by vibrational structure. A notable common feature seen in the vibronic structure is the excitation of the \( u_3\) (\(\rm C\)\(\rm -\)\(\rm X\) symmetric stretch) mode to form extensive progressions. Additionally, the \( u_1\) (\(\rm C\)\(\rm -\)\(\rm H\) symmetric stretch), \( u_2\) (\(\rm CH_2\) bend) and \( u_8\) (\(\rm CH_2\) wag) modes are observed in \(\rm CH_2Cl_2\) and \(\rm CH_2I_2\), although they do not form long progressions. Quantum chemical calculations of ground and excited states are used to support the analysis and an improved theory-experiment comparison is provided for \(\rm CH_2Br_2\).
Keywords: Excited states; Dihalomethanes; Rydberg series; VUV photoabsorption; Vibronic structure